Shared decision making and support for self-management: a rationale for change - Lewis-Barned, Nick (Future Hosp J, 2016)
Shared decision making and support for self-management are among a range of approaches that have been developed over the last 20 years to fundamentally change the relationship between health professionals and patients. They have strong synergies and address the inequalities of the current relationship. They replace this with a partnership approach in which health professionals and patients work together to identify and enact decisions and plans that are jointly agreed on the basis of both medical evidence and what matters most to individuals. To do this effectively requires the development of new ways of working based on a culture of collaborative working, skills that support patients to think through and articulate preferences, and the development of systems and tools that make it easier to do this. There is already a body of practice that helps to identify what needs to be done and this practice now needs to be extended across the healthcare system